Erratum - Li S; Horner P; Delva J (Dove Medical Press, 2012)
Li S, Horner P, Delva J. Social capital and cigarette smoking among Latinos in the United States. Subst Abuse Rehabil. 2012;3(Suppl 1):83–92.This paper was incorrectly assigned to 2012;3(Suppl 1):83–92 and should have appeared in 2012;3(1).Read the original article